Sustainable Healthcare Delivery through Digital Technology: focus on the Interior Design of Orthopaedic Wards in Public Hospital Buildings in Ekiti State, Nigeria Titilayo Elizabeth Adewumi¹*, Aminat Olorunfunmilayo Ajenifujah-Abubakar¹, Tolulope Aduke - Falusi (SureBuilt Series, 2026)
Ensuring good health and well-being is one of the core Sustainable Development Goals (SDGs) that aims to support healthy lives and well-being for people of all ages. This involves providing affordable and environmentally friendly medical services to the public, fairly and equitably. The integration of digital technologies into healthcare environments is transforming healthcare delivery globally. However, public hospitals in Nigeria continue to face challenges associated with inadequate infrastructure, inefficient spatial planning, poor environmental quality, and limited adoption of digital healthcare systems. This study examined the role of digital technology and interior design in promoting sustainable healthcare delivery within orthopaedic wards of selected public hospitals in Ekiti State, Nigeria. A mixed-methods approach was adopted, combining questionnaire surveys, observation, interviews, and literature review. Data were collected from 50 respondents comprising patients, caregivers, and healthcare personnel. Quantitative data were analysed using descriptive statistics, while qualitative data were subjected to thematic analysis. Findings revealed that adequate space provision (68%), effective lighting (68%), ventilation (58%), staff digital competence (72%), technology- enabled communication (76%), electronic medical records (78%), and reduced service delays (78%) significantly contributed to improved healthcare delivery and patient satisfaction. However, privacy, furniture comfort, and ward layout efficiency were identified as areas requiring improvement. The study concludes that integrating digital technologies with evidence-based interior design strategies enhances healthcare sustainability, operational efficiency, patient recovery, and user satisfaction. The study recommends the incorporation of digital design standards into healthcare policies, investment in smart healthcare technologies, and interdisciplinary collaboration among architects, healthcare professionals, and policymakers. Spatial Characteristics of Pedestrian Crashes on an Urban Arterial Road: A Case Study of J. A. Kufuor Avenue, Accra,